Internet Use and Ethnic Heterogeneity in a Cross‐Section of Countries. Issue 1 (18th December 2015) - Awaworyi Churchill, Sefa; Okai, Davidson; Posso, Alberto
Abstract : This paper investigates the association between ethnic heterogeneity and information technology related outcomes such as Internet access and Internet use. We argue that the global digital divide, as measured by cross‐country differences in Internet access and use, could be explained by cross‐country differences in ethnic heterogeneity. We use indices of ethnic and linguistic fractionalisation as measures of ethnic heterogeneity. Using data on a cross‐section of eighty‐five countries, we find evidence of a negative association between ethnic heterogeneity and the use and access of Internet. Thus, cross‐country differences in the global digital divide can be explained by the levels of ethnic fractionalisation. Other determinants of the digital divide include income, infrastructure, literacy level, level of urbanisation and inequality.